Chemical traits of pigeonpea (Cajanus cajan) pod wall affecting pod fly (Melanagromyza obtusa) damage - PANDEY, VAGEESH; SRIVASTAVA, C P; NATH, TRIYUGI; RAHA, P (The Indian Journal of Agricultural Sciences, 2011)
Pigeonpea (Cajanus cajan (L.) Millsp.) is the second important pulse crop in India. Pod fly [Melanagromyza obtusa (Malloch)] is a major pest of long-duration pigeonpea in India. The grain damage caused by this insect pest varies from 20 to 80%. The concealed mode of life of pod fly within the pod makes it difficult to control, with chemical insecticides. Therefore, host-plant resistance is an important tool for the management of this pest. Analysis of pod walls of five pod fly resistant/tolerant and six susceptible cultivars/genotypes showed that the genotypes with more wax, total phenols and less reducing and non-reducing sugars and total amino acids suffered less pod and grain damage by pod fly. Therefore, these biochemical pod traits can be used as marker to identify the resistance sources to be used in breeding programme.